Tivi by Shahnon Ahmad as Counter-Hegemony of Mahathirism (Malay Literature, 2023)
The novel Tivi, written by National Laureate Shahnon Ahmad, was published in 1995 with its second edition published in 2018. Its narrative revolves around the moral decay of a rural family after one of their daughters introduces urban culture, especially the culture of watching television. Past academic studies on this novel do not show much interest in its ideological critiques, including counter-hegemony concerns. Therefore, in this article, Tivi is argued as a counter-hegemony towards the Mahathirism ideology, especially from the capitalist aspects of Mahathir. The term “Mahathirism” which was coined by Dr. Khoo Boo Teik will be the concept that will be applied for this discussion, along with references from other books and articles that are related to Tun Dr. Mahathir Mohamad. The theoretical framework of “hegemony” by Antonio Gramsci will be applied to the discourse on the counter-hegemony of Shahnon Ahmad on Mahathirism. Shahnon Ahmad’s position on the dichotomies — rural and urban, modern and traditional, as well as spiritual and material — in this novel shows the counter hegemonic values towards Mahathirism. The label of Islamic fiction on Tivi and Shahnon Ahmad’s background as an Islamist are factors that allow him to be considered as a “traditional intellectual” based on the Gramscian framework.